Norm, normal and disruption - Richard Mohr; Francesco Contini; Patrícia Branco (Oñati Socio-Legal Series)
The eleven papers in this special issue analyze how different sources of disruption collide with normality, the consequences on individual, social and institutional life, and efforts to re-establish the old or to create a new normal. They arose from a series of online seminars in September and October 2020 investigating normality, disruption and normalization in the wake of the current environmental, technological, epidemiological and socio-economic shocks. Disruption is a window into the underlying fabric of social arrangements. It allows us to investigate the concept of normality and its implications, the tensions and conflicts between economic, social, legal and technological means used to re-establish normality. Technologies of normalization may paradoxically cause further disruptions. Human dignity is a landmark value in these inquiries. The introduction and the papers suggest possible measures to anticipate disruptions and consequent harms. They alert us to the risks to human dignity arising from disruption and from attempts to reimpose forms of normality.